Social categories shape the neural representation of emotion: evidence from a visual face adaptation task - Otten, Marte; Banaji, Mahzarin R. (Frontiers in Integrative Neuroscience, 2012)
A number of recent behavioral studies have shown that emotional expressions are differently perceived depending on the race of a face, and that that perception of race cues is influenced by emotional expressions. However, neural processes related to the perception of invariant cues that indicate the identity of a face (such as race) are often described to proceed independently of processes related to the perception of cues that can vary over time (such as emotion). Using a visual face adaptation paradigm, we tested whether these behavioral interactions between emotion and race also reflect interdependent neural representation of emotion and race. We compared visual emotion aftereffects when the adapting face and ambiguous test face differed in race or not. Emotion aftereffects were much smaller in different race trials than same race trials, indicating that the neural representation of a facial expression is significantly different depending on whether the emotional face is black or white. It thus seems that invariable cues such as race interact with variable face cues such as emotion not just at a response level, but also at the level of perception and neural representation.